New approach for optical electroostimistic phase with optical quasi potential energy - Korpinar, Talat; Korpinar, Zeliha; Asil, Vedat (Elsevier Gmbh, 2022)
In this paper, we firstly review the optical circular motion with optical optimistic density in Heisenberg space. We define new quasi optical potential electromagnetic energy of quasi normal magnetic biharmonic fields. Moreover, we design the new characterization of uniformly optical electroosmotic phase and optical parallel transportation in cold plasma. Also, we collect new physical geometric designs for a optical optimistic density of normal magnetic biharmonic fields in Heisenberg space. Finally, we construct optical potential electromagnetic energy with respect to its electric field and sonic crystals.
Keywords: Optical circular motion; Biharmonic particle; Optical potential electromagnetic energy; Heisenberg space; Optical electroosmotic phase; Magnetic flux density